Analisis Penggunaan Model Zmijewski (X-Score) dan Altman (Z-Score) untuk Memprediksi Potensi Kebangkrutan pada PT Waskita Karya Persero Tbk - Andi Mustika Amin; Nisaul Husna Ramadhani Ilham; Nurman Nurman; Anwar Ramli; Anwar Anwar (Gemawisata: Jurnal Ilmiah Pariwisata, 2024)
This study aims to predict the potential bankruptcy of PT Waskita Karya Persero Tbk. Quantitative descriptive research type. The population used is the financial statements of PT Waskita Karya Persero Tbk with a sample of financial position reports and income statements from 2018-2023. Research data collection was carried out using documentation and literature studies. The analysis technique is the Zmijewski model (X-Score) with the three ratios, namely return on assets, debt ratio, current ratio and Altman model (Z-Score) with four ratios, namely the ratio of working capital to total assets, retained earnings to total assets, earning before interest and taxes to taotal assets, book value of equity to book value of debt. The research results of the Zmijewski model (X-Score) show that PT Waskita Karya Persero Tbk in 2018 is predicted to be a healthy company because the X-Score value is below the value of 0, in 2019-2023 it is predicted that the company has the potential fo bankruptcy because the X-Score value is above the value of 0. Meanwhile the Altman (X-Score) model shows that PT Waskita Karya Persero Tbk in 2018 is in gray zone because the Z-Score value is between 1.1 and 2.60, in 2019-2023 it is ini the danger zone because the Z-Score value is below the value of 1.1.